Hydroethanolic extract of Sida rhombifolia L. ameliorates scopolamine-induced cognitive dysfunction in rats - Laxmi A. Pattanashetti, Basanagouda M. Patil, Harsha V. Hegde, Ranjit Kangle (Journal of Applied Pharmaceutical Science, 2021)
This article is retracted. Please read the retraction notice available here: http://dx.doi.org/10.7324/JAPS.2023.1312.retractionAlzheimer's disease is a neurodegenerative condition that involves cholinergic neuronal dysfunction, oxidative stress, amyloid beta protein accumulation as a characteristic of neuropathology. Sida rhombifolia is traditionally known for the treatment of neuronal disorders. This study was designed to evaluate the effect of S. rhombifolia extract (SRE) on scopolamine (SCO) induced amnesia in rats. Sida rhombifolia hydroethanolic extract (SRE) was subjected to in-vitro tests. Furthermore, in rats amnesia was induced with SCO (1mg/kg. i.p) for 30 days and treated with 100, 200, and 400 mg/kg of SRE for 15 days. Antioxidant activity of SRE was demonstrated by decreasing DPPH and H2 O2 levels. Treatment group rats reversed SCO induced amnesia by improvement in spatial memory, decreased transfer latency and increased step through latency significantly (p < 0.001) in behavior models such as Morris water maze, elevated plus maze, and passive avoidance task, respectively. SRE administration decreased acetylcholinesterase enzyme, β amyloid1–42 levels significantly (p < 0.001), scavenges SCO induced oxidative stress by increased glutathione and decreasing lipid peroxidase levels. Histopathological studies revealed mild neuronal damage in treatment groups as compared to SCO-induced rats and is validated its implication for the treatment of cognitive impairment.
Keywords: Sida rhombifolia acetylcholinesterase, oxidative stress, β amyloid1–42, Alzheimer’s disease.